Peran Bait Mal Dalam Jaminan Sosial Di Era Fikih Klasik - F. Setiawan Santoso (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2017)
This study intends to explore bait al-mal as the principal of financial institution in Islam within the view of fikih muamalah and the history of bait al-mal in the era of classical jurisprudence in order to get clarity about the role of government in social security, especially that developed in Andalusia. Management of bait al-mal has clarified the role of the government as a mandate of God's Right. Utilization of God's right other than for Him alone, also expanded for the benefit of public altogether. Social security system in Islam has implemented it both in its muamalah fiqh and its economic history. All of that is based on the government's obligation to engage in social security system to guarantee law enforcement in all aspects of life and maintenance of economic and political stability.